Atypical manifestations of dengue infection: causes and pathogenesis - Fitriani, Yeni; Fithriyah, Fithriyah (Syntax Corporation, 2025)
Dengue fever is a disease caused by the infection of dengue virus (DENV). This virus is primarily transmitted by the Aedes aegypti mosquito. Dengue virus is classified into 4 different serotypes, namely DENV-1, DENV-2, DENV-3, and DENV-4. The symptoms experienced by individuals infected with dengue can vary widely, ranging from asymptomatic (no symptoms), flu-like fever, bleeding, and shock to death. Along with the increase in the number of dengue cases worldwide, more atypical or unusual symptoms of the disease have been observed, also referred to as expanded dengue syndrome (EDS). These unusual symptoms involve various human organs such as the heart, kidneys, liver, muscles, lungs, and the nervous system. The exact cause and mechanisms or pathogenesis of these atypical manifestations are still not fully understood. This paper aims to discuss various hypotheses related to the pathogenesis and causes of atypical manifestations of dengue infection. Several possible pathogenesiss of this disease include direct invasion by the dengue virus into cells of tissues/organs, causing damage to the tissue/organ. Additionally, indirect factors are caused by the human immune response to the virus, such as the effects of cytotoxic T cells, antibody-dependent enhancement (ADE), and excessive production of cytokines and chemokines leading to cytokine storm, resulting in vascular leakage and bleeding. Some risk factors that may contribute to severe disease caused by dengue infection include secondary heterologous infection, virulent virus strains, host factors such as genetics, age, gender, comorbidities/co-infections, and epidemiological factors such as living in areas with high dengue endemicity.